Lost & found: Jurgis Žilinskas anthropological collection - Daubaras, Mantas; Kozakaitė, Justina; Brazaitis, Džiugas; Pauža, Dainius Haroldas; Kriaučiūnienė, Vega (Archaeologia Lituana, 2025)
The article presents the collection of skulls, which was previously believed to be lost, amassed by the renowned Lithuanian physician, anatomist, and anthropologist Jurgis Žilinskas (1885-1957) between the two World Wars. The latter currently comprises 361 skulls, representing 30.4% of the former anthropological collection. The most significant discovery within this collection is the presence of three dated skulls from the Early Mesolithic period. The article presents historical, archaeological, and anthropological information on the surviving portion of J. Žilinskas’ anthropological collection, a catalog of registered skulls, and the most recent AMS 14C dates. It also includes theoretical considerations regarding the fate of the missing skulls, suggestions for further research on some important archaeological objects, and potential avenues for further research.
Keywords: Jurgis Žilinskas; Early Mesolithic; Stone age; Iron age; skull collection; archaeology; anthropology